Role of Phospholipases A2 in Vascular Relaxation and Sympatholytic Effects of Five Australian Brown Snake, Pseudonaja spp., Venoms in Rat Isolated Tissues - Vuong, Nhi Thuc; Jackson, Timothy N. W.; Wright, Christine E. (Frontiers in Pharmacology, 2021)
Human envenoming by Australian brown snakes (Pseudonaja spp.) may result in potentially life-threatening hypotension and subsequent cardiovascular collapse. There have been relatively few studies of the cardiovascular and sympathetic effects of Pseudonaja spp. venoms. In this study, we have examined the effects of venom from 5 brown snake species – P. affinis, aspidorhyncha, inframacula, nuchalis and textilis – on cardiac inotropic and chronotropic responses, vascular tone, and sympathetic nerve-induced vascular contractions in rat isolated tissues. The role of phospholipases A2 (PLA2s) in venom-induced effects was assessed with the sPLA2 inhibitor varespladib. In rat isolated left and right atria, there were no physiologically relevant effects of Pseudonaja venoms (0.1-30 µg/ml) on left atrial force of contraction (inotropy) or right atrial rate (chronotropy). In contrast, in isolated small mesenteric arteries precontracted with a thromboxane mimetic, each of the 5 brown snake venoms (at 30 µg/ml) caused marked vasorelaxation (-60-90% of contractile tone). Pretreatment with varespladib (1 µM) significantly inhibited the vasorelaxation caused by P. aspidorhyncha, P. nuchalis and P. textilis venoms. Electrically induced sympathetic nerve-mediated contractions of mesenteric arteries were significantly attenuated by only P. textilis and P. affinis venoms (30 µg/ml) and these sympatholytic effects were inhibited by varespladib (1 µM). Based on their inhibition with the sPLA2 inhibitor varespladib, we conclude that PLA2 toxins in P. aspidorhyncha, P. nuchalis and P. textilis venoms are involved in brown snake venom-induced vasorelaxation and the sympatholytic effects of P. affinis and P. textilis venoms. Our study supports the promising potential role of varespladib as an initial (pre-referral) and/or adjunct (in combination with antivenom) therapeutic agent for brown snake envenoming.